2018
DOI: 10.1128/aac.01281-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Bioluminescent Monitoring of Therapeutic Efficacy and Pharmacodynamic Target Assessment of Antofloxacin against Escherichia coli in a Neutropenic Murine Thigh Infection Model

Abstract: Antimicrobial resistance among uropathogens has increased the rates of infection-related morbidity and mortality. Antofloxacin is a novel fluoroquinolone with broad-spectrum antibacterial activity against urinary Gram-negative bacilli, such as This study monitored the efficacy of antofloxacin using bioluminescent imaging and determined pharmacokinetic (PK)/pharmacodynamic (PD) targets against isolates in a neutropenic murine thigh infection model. The PK properties were determined after subcutaneous administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…aeruginosa isolate when the pazufloxacin dosage exceeded the MIC, similar to that of aminoglycosides; this finding verifies the concentration-dependent efficacy of this antimicrobial agent [ 16 ]. The most suitable PK/PD parameter for fluoroquinolones in animal models is the AUC 24 /MIC or C max /MIC ratio [ 8 , 9 , 10 ]. In our study, the f AUC 24 /MIC and f C max /MIC ratio required for a static effect and maximum killing of the P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aeruginosa isolate when the pazufloxacin dosage exceeded the MIC, similar to that of aminoglycosides; this finding verifies the concentration-dependent efficacy of this antimicrobial agent [ 16 ]. The most suitable PK/PD parameter for fluoroquinolones in animal models is the AUC 24 /MIC or C max /MIC ratio [ 8 , 9 , 10 ]. In our study, the f AUC 24 /MIC and f C max /MIC ratio required for a static effect and maximum killing of the P .…”
Section: Discussionmentioning
confidence: 99%
“…Andes et al reported that the target value of gatifloxacin AUC24/MIC for stasis was 41.2, for 1 log 10 it was 72.2, and for 2 log 10 it was 126 [ 9 ]. Zhou et al reported that the target value of antofloxacin fAUC 24 /MIC for stasis was 38.7, for 1 log 10 it was 66.1, and for 2 log 10 it was 147 [ 10 ]. The target value may vary among fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…Our correlation data indicated that the coix seed extract enhanced anti-cancer efficacy of gemcitabine in pancreatic cancer cells was strong associated with the downregulation ABC transport mediated drug efflux, which may lead to increased gemcitabine accumulation in cells. Previous studies have already indicated that pharmacokinetic indexes could reflect the process of tumorigenesis and cancer development when monitoring of therapeutic efficacy using bioluminescent imaging [18,30,47]. Although there are several pathways for regulating gemcitabine efflux and influx, ABC transporters may be essential and critical for inducing gemcitabine resistance [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, as compared with viable counting methods, the sensitivity of bioluminescence is generally lower. Consequently, they are not useful to evaluate compounds with mild antibacterial effect [40].…”
Section: In Vivo Animal Modelsmentioning
confidence: 99%